The impact of organizational culture on the competitive strategy and its influence on the export performance of SMEs in Barranquilla, Colombia - Sáenz Castro, Diego (2016)
The goal of this research is to determine the influence of organizational culture on business competitive strategy and its impact on the export performance of SMEs in Barranquilla, Colombia. The study took place from August to November, 2015, and it consisted on a telephone survey applied to a sample of 136 companies, from a population of 165 companies in the area, and a response rate of 50 companies. The theoretical approaches used were the proposed by Cameron and Quinn (2006), related to the cultural factors, and by Porter (1990) and Miles & Snow (1978) for the strategic factors. The results showed that culture has no influence on the strategy, and that the most common strategic orientation used by the companies surveyed is the analyzer type. Regarding the impact of the strategy on export performance, we determined that it does not exist. Regression calculations were made to test the hypotheses, and they were rejected. SMEs surveyed do not have a good export performance according to the Export Performance Index (IDE). All these data were analyzed using the SPSS software.